2016
DOI: 10.1590/1808-1657000832014
|View full text |Cite
|
Sign up to set email alerts
|

Zoonosis associated to Rattus rattus and the impacts of the public actions to control the species

Abstract: The occurrence of the black rat, Rattus rattus , in major Brazilian cities has increased in the recent years. To evaluate if the efforts of public rodent control have been reaching the species in the city of São Paulo, a survey was conducted in flooding areas using live trapping before and after implementation of the control program. Captures were carried out from 2009 to 2011, and animals were evaluated for their risk of zoonosis transmission. The number of R. rattus captured after control did not differ from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…We also did not find the correlation between the number of baits applied with the relative abundance (trap success) estimated at each evaluated point. These results are consistent with a previous study carried out in São Paulo [ 39 ], which used a similar methodology where there were no changes in the relative abundance of R . rattus after an intervention using rodenticides with the same active principles and formulations as those used in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also did not find the correlation between the number of baits applied with the relative abundance (trap success) estimated at each evaluated point. These results are consistent with a previous study carried out in São Paulo [ 39 ], which used a similar methodology where there were no changes in the relative abundance of R . rattus after an intervention using rodenticides with the same active principles and formulations as those used in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Few previous studies have reported data on the efficiency of control programs in affecting urban populations of rodents [ 17 , 38 , 39 ]. Additionally, none of them systematically and longitudinally assessed the quality of the intervention in terms of coverage, intensity, and the number of visits performed in each household in the studied area.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that the presence of rodents was highly significant, leading to the assumption that these animals can act as vectors of VACV. A serological study detected neutralizing antibodies against VACV in Rattus rattus captured in the metropolitan region of São Paulo/SP/Brazil, evidencing that VACV circulates in this species in synanthropic conditions (BABOLIN et al, 2016). However, it was detected, in rural properties of São Paulo, a high sero-prevalence among domestic animals (cows, horses, sheep, pigs, dogs and cats) and humans, and there was no positive result for wild rodents, emphasizing the involvement of other species that act as reservoirs in the VACV transmission cycle (PERES et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…and fleas (Xenopsylla spp.). Members of the genus Echinolaelaps are known to harbour dermatitisand leptospirosis-causing pathogens (Babolin et al 2016), while members of the genus Xenopsylla are important vectors of the pathogenic bacilli, Yersinia pestis, and the agent of murine typhus, Rickettsia typhi, that are both harmful to humans and other animals (Dill et al 2013;Boyer et al 2014;McCauley et al 2015;Thomas et al 2020). Although these two genera exhibit the same life-history strategy of living on and off their hosts, their load is expected to vary with small mammal density (Perez-Orella and Schulte-Hostedde 2005) and to be lower in the protected park than in the disturbed agricultural or pastoral land (Khalil et al 2016).…”
Section: Introductionmentioning
confidence: 99%